2021
DOI: 10.1186/s12199-021-00993-7
|View full text |Cite|
|
Sign up to set email alerts
|

Classes of childhood adversities and their associations to the mental health of college undergraduates: a nationwide cross-sectional study

Abstract: Background Childhood adversities pose deleterious consequences on health and well-being, but limited studies explore whether unique patterns of adverse childhood experiences (ACEs) impact the mental health of emerging adults and the mediating role of current stressful events (CSEs). This study examined classes of ACEs and how they relate to CSEs, psychological distress, and subjective well-being among Eritrean College undergraduates. Methods Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…For adolescents who have experienced childhood trauma, educational institutions and health services should recognize childhood trauma early and provide relevant education and interventions to prevent further development, thereby improving PH. In addition, clinicians should be reminded to consider childhood trauma and IA problems in the face of adolescent PH (e.g., anxiety, depression), which can help provide effective interventions [ 76 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents who have experienced childhood trauma, educational institutions and health services should recognize childhood trauma early and provide relevant education and interventions to prevent further development, thereby improving PH. In addition, clinicians should be reminded to consider childhood trauma and IA problems in the face of adolescent PH (e.g., anxiety, depression), which can help provide effective interventions [ 76 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early adversity may not only be considered a risk factor for mental illnesses but may also have a direct impact on well-being. In this regard, a study that employed a sample of Eritrean college students found that the presence of multiple early adversities and domestic violence can predict both psychological distress and subjective well-being, with these effects being mediated by current stressful events [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between ACEs (e.g., child abuse [ 7 ], parental divorce [ 11 ], and parental mental illness [ 12 ]) and a wide range of poorer health outcomes has been studied extensively [ 13 ]. According to previous studies, 39% of adolescents have at least one type of ACE, and Chinese undergraduates with a history of ACEs are more likely to report symptoms of psychological distress and ultimately higher premature mortality than those without a history of ACEs [ 14 , 15 ]. Given the harmful effects of ACEs on health, recent studies have begun to identify protective factors that can help adolescents overcome the negative impacts of ACEs on mental health outcomes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%